An Examination of the Impact of Power Sector Reform on Manufacturing and Services Sector in Nigeria: an Empirical Analysis - Emmanuel Ameh Ojiya; Ngwu Jerome Chukwuemeka; B.A. Daneji; George Duhu Isiwu (International Journal of Advances in Applied Sciences, 2018)
The main objective of this study is to empirically examine the impact of Power Sector Reform on Manufacturing and Services Sector in Nigeria between 1999-2016. The study employed secondary annual time series data sourced from World Bank database (2016). The methodology adopted for the study was Augmented Dickey-Fuller (ADF); a test for long-run relationship using ARDL Bounds Testing approach  with analysis of long-run and short-run dynamics in the model. A striking revelation from the study is the inverse relationship that exists between manufacturing output and electricity consumption in Nigeria within the period referenced. This negative relationship is not unconnected with widespread allegation of misappropriation of budgeted funds for the Power Sector by successive administrations in Nigeria since 1999.  It must be stated in clear terms that constant and consistent electricity generation, transmission and distribution is sine-qua-none for the growth of the national economy. Virtually all sectors of the economy depend on the supply of electricity to do business and so the lack of this vital ingredient of growth contributes in no small measure in stagnating economic growth and development. Efforts at reforming the power sector can only be fruitful when ALL stakeholders in the power sector including the political class put away their personal agendas and take the bull by the horn towards rescuing the nation from the looming danger of stagnant economic growth. Furthermore, there is the need for the Nigerian government to come up with new, better and alternative ways of improving energy generation and supply, as well as proper maintenance of electricity infrastructure in the country.